The Effect of Calcined Green Mussel Shell as Partial Cement Replacement on The Compressive Strength and Modulus of Elasticity of Concrete - Aldebaran; Eva Arifi; Devi Nuralinah (Jurnal Mahasiswa Jurusan Teknik Sipil, 2023)
Concrete is a most widely used construction materials on earth. However, the concrete industry with a massive production overtime produces harmful effects to the environment. Cement production generates greenhouse gases that contribute to the air pollution. Hence, the innovation regarding cementitious materials has been conducted in order to reduce the utilization of environmentally unfriendly materials in the concrete industry. The use of green mussel shell (Perna viridis) waste as an alternative Portland cement substitution could reduce the utilization of conventional cementitious materials. In this research, the concrete specimen cylinder (15cm x 30cm) with cement replacement percentages of 10%, 20%, and 30% by volume were produced. The green mussel shell waste originated from Banyuurip Village, Gresik Regency, East Java was used. Moreover, calcination process required heat treatment at 900°C for two hours. Compressive strength and modulus of elasticity of concrete were the characteristics observed in this research. The tests were carried out when the sample age reached 28 days. Furthermore, it has been observed that higher cement replacement percentage in concrete mixture reduced the compressive strength and modulus of elasticity of the concrete. The filler effect characteristic of the green mussel shell resulted a tendency of the particles to fill the voids inside the concrete rather than activate as a binder in the concrete mixture. However, these research outcomes were meaningful for further understandings regarding the modification in concrete formulation and also contribute in handling the massive numbers of aquaculture waste in order to achieve sustainable construction. Keywords: Green Mussel Shell Waste, Cement Replacement, Compressive Strength, Modulus of Elasticity, Sustainable Construction